Endodontic Management of a Mandibular First Molar with Four Canals in a Distal Root by Using Cone-Beam Computed Tomography: a Case Report - Hani Baziar; Farzaneh Daneshvar; Abbas Mohammadi; Hamid Jafarzadeh (Stilus Optimus, 2014)
Background: Aberrations in the root canal anatomy are clinically challenging for clinicians. Mandibular first molars usually have 2 roots and 3 or 4 canals, but various combinations may exist. A distal root with three canals is rare and its incidence in literature is about 0.2 - 3%. As a diagnostic tool, cone-beam computed tomography (CBCT) may be a better choice for diagnosis of extra roots or canals comparing to conventional radiography. Methods: An endodontic management of a mandibular first molar with six canals was performed. CBCT was used to confirm the diagnosis and to understand the morphology of the canals. Results: Evaluation of the axial and coronal slices of CBCT images confirmed the presence of 2 roots and 6 canals. The distal root had four distinct root canal orifices with two apical foramens, being described as type XIV canal configuration. Conclusions: Dentists should be aware of unexpected canal morphology when performing endodontic treatment. The present case demonstrated the use of CBCT in diagnosis and negotiation of extra canals in a mandibular first molar.